PERANAN PUSKESMAS SIWALANKERTO DALAM RANGKA PENCEGAHAN VIRUS COVID-19 DI KOTA SURABAYA - Erika Ayu Septiani; Tri Prasetijowati; Ali Fahmi (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2022)
The purpose of this study was to determine the role played by the Siwalankerto Health Center in preventing the Covid-19 Virus and to find out what obstacles the Siwalankerto Health Center had to overcome when preventing the transmission of the Covid-19 Virus. The method used in this research is qualitative method. The results of the study: 1) The application of the role of the Siwalankerto Health Center in handling the spread in the city of Surabaya went well according to its function and focus on supervision and counseling in the health sector; 2) The Siwalankerto Health Center strives for supervision in the form of rapid test training which is carried out smoothly for each representative. There are several factors of failure and obstacles in the role of the Siwalankerto Health Center in tackling the rapid spread of Covid -19 in the City of Surabaya. 19. Regarding the policy of preventing and transmitting the covid-19 virus, the Siwalankerto Health Center continues to try to appeal to the community, but most of the people do not pay attention to the smell that has been emphasized by the government, this is the failure factor for the Siwalankerto Health Center.